Citrange troyer growth and chemical-microbiological attributes of the soil in response to different organic fertilizers - Rivera-Cruz, María del Carmen; González-Mancilla, Apolinar; Almaraz-Suárez, Juan José; Ortiz-García, Carlos Fredy; Trujillo Narcía, Antonio; Vázquez-López, Patricia; Cruz-Navarro, Gonzalo (REVISTA TERRA LATINOAMERICANA, 2020)
Citrus production depends principally on the healthiest, appropriate and vigorous rootstock available; part of its reproduction is associated with the use of chemical fertilizers, that contribute to ecosystem contamination. Uses of organic fertilizers are alternatives to reduce the use of chemical fertilizers. Therefore the objective of this study was to evaluate the effect of three organic fertilizers (chicken manure, sugarcane residue (1 and 2), and banana waste) supplied in three doses (1, 2 and 3%), in chemical and microbiological soil properties and in Citrange troyer rootstock growth in greenhouse. A complete randomized design was used with 14 treatments and six replicates each, including two control groups (absolute and fertilized). Serial dilutions in specific media were used to quantify Azospirillum, Azotobacter, phosphate and potassium solubilizing bacteria. Arbuscular mycorrhizal fungi were evaluated according to the clearing and dyeing technique with trypan blue. Soil pH increased 0.9 units when adding 1% sugarcane residue-2; while organic carbon increased 0.7% with chicken manure 1%; Azospirillum, Azotobacter and phosphate solubilizing bacteria increased in the treatments supplied with sugarcane residue-1 1% and chicken manure 1%. The cachaza-1 2% induced greater mycorrhizal colonization and increased plant growth. Nine of twelve treatments with the organic fertilizers used, positively modif ied soil chemical and microbiological properties, resulting in a better growth of Citrange troyer compared with the control groups.